(untitled) (Research, Society and Development, 2020)
This study embraces the work condition of teaches in public schools at the city of Salinópolis at State of Pará searching for understanding the context of professor work in front of the actual educational policy and verifying the affinity of that government policy with the contradictory process of relation capital-work. The methodological procedure was conducted from a bibliographic survey addressing the categories of work, precarity and contradiction, moreover semi structured interviews and direct observation of the teachers of the public schools of the such region recently hired via public contest. The result was based on the market principles of the capital-labor relationship in public education, showing the precariousness of teaching work and the existence of a process of precariousness of the work. Leading to conclude about the effectiveness, by the public power, of the mechanisms responsible for guaranteeing the profound expropriation of the workforce of the teacher in the State of Pará inherent to the conditions of capitalist society.